1995
DOI: 10.3109/15563659509017985
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Repercussions of Seizures During Cyclic Antidepressant Poisoning

Abstract: Cyclic antidepressant overdose involves a risk of generalized seizures and cardiovascular disturbances. We have conducted a retrospective study to test the hypothesis of a relationship between generalized seizures and the onset of arrhythmia, hypotension or cardiac arrest during cyclic antidepressant intoxication. Patients who had seizures after ingestion of toxic amounts of tri- or tetracyclic antidepressants were included. Limb-lead QRS complex duration and systolic blood pressure were recorded before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 28 publications
1
13
0
2
Order By: Relevance
“…One poison center-based study reported in 1993 that, over a 2-year period, TCAs alone accounted for 25% of all overdoseinduced convulsions (5). In a 1995 retrospective study of 388 consecutive patients with TCA poisoning admitted to the Fernand Widal Hospital in Paris over a 4-year period, 6.2% developed grand mal seizures, although this figure could underestimate the risk since some patients had also ingested benzodiazepines, which have anticonvulsant properties (6).…”
Section: Statement Of the Scope Of The Problem And Importance Of The mentioning
confidence: 99%
See 4 more Smart Citations
“…One poison center-based study reported in 1993 that, over a 2-year period, TCAs alone accounted for 25% of all overdoseinduced convulsions (5). In a 1995 retrospective study of 388 consecutive patients with TCA poisoning admitted to the Fernand Widal Hospital in Paris over a 4-year period, 6.2% developed grand mal seizures, although this figure could underestimate the risk since some patients had also ingested benzodiazepines, which have anticonvulsant properties (6).…”
Section: Statement Of the Scope Of The Problem And Importance Of The mentioning
confidence: 99%
“…There were a number of articles in which the recognition of the amitriptyline ingestion was retrospective, so there was uncertainty about the actual amount ingested. Among these were five level 2b articles (16,53,(59)(60)(61), a single level 3b article (62), and five level 4 articles (6,48,(63)(64)(65). Also, there were over 50 level 4 or 6 articles in which detailed information was presented concerning 65 cases (see Table 5).…”
Section: Amitriptylinementioning
confidence: 99%
See 3 more Smart Citations